Green innovation for sustainable urban ecosystems: Overcoming challenges and promoting eco-friendly practices - ​Aiya Maghfirah; Yudya Alif Ridhoni Prakusya (Sustainable Urban Development and Environmental Impact Journal, 2025)
​​​Background: Urban expansion has led to severe environmental degradation, often outpacing sustainability efforts. Green innovation, which integrates eco-friendly technology and economic models, offers a solution. However, its success depends on human involvement, including policymakers, scientists, and engineers. This study examines the role of humans in implementing green innovation in Jabodetabek, a densely populated and economically active region in Indonesia. Methods: This research employs a literature review to analyze existing studies on green innovation, focusing on its application in urban areas, particularly Jabodetabek. The review identifies key challenges and opportunities related to the adoption of green innovation in densely populated regions. By synthesizing the findings, the study examines the role of human involvement—policymakers, scientists, engineers, and communities—in overcoming obstacles and promoting green innovation. Findings:  The findings reveal that while green innovation is essential for creating a sustainable urban ecosystem, its implementation in Jabodetabek faces three major obstacles: lack of public awareness, high implementation costs, and regulatory uncertainty. Limited understanding among the public slows adoption, while significant financial investment is required to develop and apply green technologies. Additionally, inconsistent policies create barriers to implementation. To address these challenges, collaboration between the government, private sector, academics, and communities is crucial. Three main factors can accelerate the adoption of green innovation: strengthening regulations to support sustainability, developing better funding mechanisms to encourage investment, and promoting lifestyle changes that encourage eco-friendly habits. Conclusion: Green innovation is vital for sustainable cities, and human efforts play a key role in its success. In Jabodetabek, systematic and collaborative action can overcome obstacles and enhance both environmental and social well-being. Novelty/Originality of this article: This study highlights the role of humans in green innovation, emphasizing collaboration, commitment, and creativity, and explores how human efforts can drive sustainability in urban areas.